Theoretical and experimental studies of aryl-bithiophene based push-pull π-conjugated heterocyclic systems bearing cyanoacetic or rhodanine-3-acetic acid acceptors for SHG nonlinear optical applications. (February 2018) - Fernandes, Sara S.M.; Herbivo, Cyril; Aires-de-Sousa, João; Comel, Alain; Belsley, Michael; Raposo, M. Manuela M.
Abstract: A series of push-pull aryl-bithiophene based systems2–3 were designed and synthesized in order to understand how structural modifications influence the electronic, linear and nonlinear optical properties. The push-pull conjugated chromophores2–3 bear a bithiophene spacer conjugated with a phenyl ring functionalized with N, N -dialkylamino electron-donor groups together with cyanoacetic or rhodanine-3-acetic acid acceptor groups. Theoretical (DFT calculations) and experimental studies were carried out to obtain information on conformation, electronic structure, electron distribution, dipolar moment, and molecular nonlinearity response of the push-pull bithiophene derivatives. This multidisciplinary study revealed that chromophore2e exhibits the highest value for hyperpolarizability β (10440 × 10 −30  esu) due to the strong electron donating ability of the N, N -dimethylamino group, and the ethyne linker that not only lengthens the π-conjugation path but also grants less distortion to the system. Graphical abstract: Highlights: Synthesis of cyanoacetic acid and rhodanine arylbithiophenes through efficient and simple procedures. The linear and nonlinear optical properties of the compounds were investigated. Enhancement of the SHG was achieved through the introduction of an ethyne linker and a cyanoacetic acceptor group. DFT calculations were carried out to obtain conformation information, dipolar moments and SHG of arylbithiophenes. Push-pull arylbithiophenes function as efficient second harmonic generation chromophores.